Integrated reporting in higher education: insights from Scotland, Northern Ireland and Wales. Issue 3 (15th April 2020) - Adhikariparajuli, Mahalaximi; Hassan, Abeer; Fletcher, Mary; Elamer, Ahmed A.
Abstract : Purpose: This paper aims to examine the level of disclosure on content elements of integrated reporting (IR) in Scotland, Northern Ireland and Wales higher education institutions (HEIs). The authors suggest that integrated thinking is an internal process that organizations can follow to increase the level of disclosure on IR that can be used as an effective mechanism to enhance accountability with stakeholders. Design/methodology/approach: International Integrated Reporting Council (IIRC) guidelines and content analysis are used to analyze IR content elements in HEI reports from 2014-2016. Findings: The results indicate a significant increase in the trend and extent of IR content elements. The HEI-specific characteristics examined, such as establishment of HEI; adoption of IR framework and governing board size are all statistically and positively associated with IR content elements disclosure. This paper introduces signalling theory to explore the idea that appropriate communication via integrated thinking can close the gap between the organization and its stakeholders via increased level of disclosure on IR content elements. Practical implications: The results will assist policymakers and regulators to assess the benefits of voluntary implementation of IR at HEIs and evaluate possible mandatory implementation of IIRC guidelines. Second, the findings can assist managers of institutions interested in implementing IR. Social implications: This study recommends universities to explicitly address IR issues in reporting, as this will increase their impact as leaders of educational thought in addition to their roles as partners, advisors, counselors and assessors. Originality/value: This study explores whether HEIs in Scotland, Northern Ireland and Wales provide disclosure on IIRC content elements as a reflection of integrated thinking and whether the connectivity and interdependence between different departments will help to signal to stakeholders how HEIs create value for society.